Comparison of the Effect of Fimasartan versus Valsartan on Blood Pressure Variability in Acute Ischemic Stroke: A Double-Blind Randomized Trial - Dong Hoon Shin; Soohwa Song; Yeong Bae Lee (Cardiovascular Therapeutics)
Higher blood pressure variability (BPV) is associated with poor functional outcome and mortality in acute stroke. This randomized controlled trial was conducted to compare the effect on BPV between fimasartan and valsartan (Boryung Pharmaceutical Co., Ltd., Seoul, Republic of Korea) in patients with acute ischemic stroke. Eighty patients were randomly assigned to receive either valsartan or fimasartan after 7 days of acute ischemic stroke onset, for duration of 8 weeks. Of them, 62 patients completed the study [valsartan (n=31), fimasartan (n=31)]. We measured BP for 24 hours using ambulatory BP monitoring device before and after 8 weeks of starting BP medication. We calculated several indexes such as standard deviation (SD), weighted 24-hour BP with SD (wSD), coefficient of variation (CV), and average real variability (ARV) to assess BPV and to compare indexes of BPV between 2 drugs. SD values of systolic BP in daytime, nighttime, and 24 h period (15.55±4.02 versus 20.55±8.77, P=0.006; 11.98±5.52 versus 16.47±6.94, P=0.007; 17.22±5.30 versus 21.45±8.51, P=0.024), wSD of systolic BP (8.27±3.01 versus 10.77±4.18, P=0.010), and ARV of systolic BP (15.85±6.17 versus 19.68±7.83, P=0.040) of patients receiving fimasartan after 8 weeks were significantly lower than patients receiving valsartan. In paired t-test, SD values of daytime, nighttime, and 24 h period of systolic BP of patients receiving fimasartan were significantly decreased after 8 weeks (15.55±4.02 versus 18.70±7.04, P=0.038; 11.98±5.52 versus 17.19±7.35, P=0.006; 17.22±5.30 versus 20.59±5.91, P=0.015). Our study showed that fimasartan had greater effect on reducing BPV after acute ischemic stroke than valsartan. Trials registry number is KCT0003254.